REVIEW ON POTENTIAL ANTIDIABETIC DRUGS IN AYURVEDA (International Journal of Ayurveda and Pharma Research, 2020)
Ayurvedic texts are mentioned this Vedic sastra as a science of life. Ayurveda mainly targeted lifestyle of human being as well as mentioned number of drugs on various disorders. Among these disorders, diabetes is a major disorder. Due to which people are suffering lot. Diabetes is a major metabolic as well as lifestyle related disease. Anti-diabetic drugs from modern science can treat this disorder but at the cost of heavy side effects. Diabetic patients are using the modern drugs at higher doses plus these drugs are much costlier. Need of today’s era is to use alternate therapies for diabetes. Among all alternative therapies Ayurveda gives ray of hope by using the Anti-diabetic drugs as mentioned in ancient texts. Ayurveda uses many drugs for diabetes especially herbal and herbomineral preparations. The review paper focuses on various Ayurvedic drugs herbal, herbomineral either in single or compound preparations studied at several research organizations. The paper focuses on antidiabetic properties of Ayurvedic drugs mentioned in Ayurvedic texts as well as their pharmacological, phytochemical properties and their scientific studies.